Evaluation of the potential of purple eggplant peel extract (Solanum melongena L.) as a pH indicator for bacterial growth - Purba, Wenni Oktraiani; Syahputri, Yuli Yantika; Lubis, Nita Andriani; Nasution, Gabriella Septiani; Setiyawati, Dewi; Sembiring, Febri (Jurnal Biologi Udayana; Vol 29 No 1 (2025): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2025.v29.i01.p01, 2025)
Anthocyanins are natural pigments found in various plants and fruits, known for their ability to change color according to the pH of their environment. This property can be utilized as a pH indicator in observing carbohydrate fermentation reactions by bacteria. This study aims to evaluate the potential of purple eggplant peel extract (Solanum melongena L.) as an alternative pH indicator to monitor bacterial growth. Purple eggplant peel was extracted using 80% ethanol containing 1% HCl, stored for 24 hours at 4 °C, centrifuged, and concentrated using a rotary evaporator at 35 °C. The extract obtained was used as a pH indicator in Tryptic Soy Broth (TSB) media for Escherichia coli growth. This test used two treatments; namely purple eggplant peel extract added into TSB media before bacterial inoculation and purple eggplant peel extract added after bacteria grew on TSB media. The results showed that purple eggplant peel extract effectively showed a clear color change according to different pH levels. However, when applied to bacterial growth media, the addition of purple eggplant peel extract showed no significant color change on TSB media, neither before nor after bacteria growth. Thus, to effectively utilize this extract as an indicator in bacterial growth media, further research is needed to explore methods to maintain the stability of the pigments contained in purple eggplant skin extract when added to bacterial growth media.